ANALISIS CACING HATI (Fasciola hepatica) PADA HATI DAN FESES SAPI YANG DI AMBIL DARI RUMAH POTONG HEWAN DI MABAR MEDAN TAHUN 2013 - Iba Ambarisa; irnawati marsaulina; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
Abstract Among the many animal diseases in Indonesia, a parasitic disease has received less attention from the breeder. Diseases in livestock is one of the obstacles encountered in the development of animal husbandry, Among parasitic disease that causes loss of body condition and a decrease in the productivity. Among parasitic diseases are very harmful disease caused by liver fluke (Fasciola hepatica). The purpose of this study to describe the liver fluke (fasciola hepatica) in cattle liver and feces were taken from the slanghterhause in Mabar Medan years 2013. The method used in this study is a survey that is both descriptive, object of research is the heart and cow feces samples to be studied were 12 liver and 12 feces beef. Based on the research content of worms and aggs in the liver and feces from the liver slaughterhouse in Mabar Medan has qualified. Beef liver condition are made in the sample were is beef liver (100%) and 12 samples of beef feces (100%) in theabattoir has qualified Mabar Medan. The conclusion that Beef liver condition which sampled a total of 12 beef liver in a battoir in Mabar Medan qualify. Conditions are made in the cow feces sample of 12 feces slaughterhouse cows in field Mabar Medan. For city farm field offices are expected to conduct ontreach to owners of cattle in order to increase the knowledge of good cattle rearing. To the managers of dairy farm is expected to provide fresh fodder and not wet from being contaminated by liver fluke (fasciola hepatica). Key words : Fasciola hepatica, Feces, Beef, slaughterhouse